1997
DOI: 10.1128/jb.179.5.1636-1645.1997
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-beta-glucosidase from Fusobacterium mortiferum: purification, cloning, and inactivation by 6-phosphoglucono-delta-lactone

Abstract: 6-Phosphoryl-␤-D-glucopyranosyl:6-phosphoglucohydrolase (P-␤-glucosidase, EC 3.2.1.86) has been purified from Fusobacterium mortiferum. Assays for enzyme activity and results from Western immunoblots showed that P-␤-glucosidase (M r , 53,000; pI, 4.5) was induced by growth of F. mortiferum on ␤-glucosides. The novel chromogenic and fluorogenic substrates, p-nitrophenyl-␤-D-glucopyranoside-6-phosphate (pNP␤Glc6P) and 4-methylumbelliferyl-␤-D-glucopyranoside-6-phosphate (4MU␤Glc6P), respectively, were used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…1). Belaich et al (6) (34). Family 30 CBMs appear to be closely related to a family 9 catalytic module, although the first example, F. succinogenes CelF, coexists with the family 51 catalytic module.…”
Section: Discussionmentioning
confidence: 99%
“…1). Belaich et al (6) (34). Family 30 CBMs appear to be closely related to a family 9 catalytic module, although the first example, F. succinogenes CelF, coexists with the family 51 catalytic module.…”
Section: Discussionmentioning
confidence: 99%
“…After growth in rich medium, microarray analysis revealed that pgl mutant L. monocytogenes had increased expression of several ␤-glucosidases compared to the wt. We speculate that this is due to the known inhibition of ␤-glucosidases by 6-phosphogluconolactone (36), the substrate of Pgl that is predicted to accumulate in its absence. In E. coli lacking pgl, 6-phosphogluconolactone is dephosphorylated prior to its export and hydrolysis into gluconate (14).…”
Section: Vol 77 2009mentioning
confidence: 99%
“…Therefore, Pgl, though likely important for the optimal efficiency of the PPP, may not be essential (13,14). In Escherichia coli, disruption of pgl (ybhE) results in accumulation of the Pgl substrate, 6-phosphogluconolactone (14), a reactive electrophilic molecule (20,27) and a potent inhibitor of bacterial ␤-glucosidases (36). In an E. coli pgl deletion mutant, the accumulating 6-phosphogluconolactone is dephosphorylated and exported, where it subsequently hydrolyzes to form gluconate (14).…”
mentioning
confidence: 99%
“…Preparation of NP G6P was by the procedure described earlier for the synthesis of NP G6P. 17,28,29) Expression and purification of the enzyme. E. coli strain BL21 (DE3) carrying pET-21a(+)/BglA was grown at 37 C to mid-log phase in LB medium containing 50 mg/ml ampicillin.…”
Section: Methodsmentioning
confidence: 99%